Inflation expectation formation of German consumers: rational or adaptive? - Henry Sabrowski (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2008)
This paper analyzes the inflation expectation formation empirically for German consumers. The expectation formation process is analyzed for a representative consumer and for different demographic groups. The results indicate that German consumers are a relatively homogeneous group. There are nevertheless quantitative differences among the groups: Inflation expectations and perceived inflation tend to fall with rising income and unemployed individuals are outliers. Rational inflation expectation is not present for any group. Consumer and expert expectations have short and long run relationships. Evidence for a positive constant gain in the adaptive learning algorithm is given for almost all groups.
Keywords: C42; D83; D84; E31; 330; Inflation expectations; conversion method; survey data; rationality tests